The Effect of Lesson Plans on Teaching Quality and Learning Outcomes - Enjang Yusup Ali; Nur Afna Juanda (Yayasan Keluarga Guru Mandiri, 2025)
The quality of teaching at the elementary education level is primarily determined by the ability and readiness of teachers in developing and implementing effective teaching methods. One of the main factors that guarantee the success of the learning process is the preparation of a structured lesson plan that focuses on student needs. This study aims to conduct an empirical study analyzing the effect of lesson plans on the quality of teacher teaching and learning activities and student learning outcomes at elementary level. The approach used is a quantitative approach with a quasi-experimental design, involving 12 teachers and 45 students from two classes in one elementary school in Sukasari District, Bandung City. Data collection was carried out through observation of teacher teaching quality and student learning outcome tests. The findings of this study were 86.58% of teachers consistently planning learning can improve teaching quality. Strengthened by the results of student learning analysis using ANCOVA, namely a sig value of 0.000 0.05, confirming that lesson plans affect teaching quality and learning outcomes in science subjects.